Financial Capital and Financial Inclusion on Hotel Business Performance in Bandung, Indonesia - Andre Hernowo; Deden Rudy Mustafa (Budapest International Research and Critics University, 2022)
The hotel business is one of the tourism sectors which in its management focuses on services. Financial factors are one of the factors that can support the success of the hotel business. This study aims to determine the effect of financial capital and financial inclusion on the performance of the hotel business in the city of Bandung. The research was conducted on the non-star hotel industry in the city of Bandung. The participants in this study were non-star hotel managers in the city of Bandung. The number of questionnaires distributed amounted to 234 and returned as many as 192. So the sample in this study amounted to 192 respondents. The results showed that there was a positive and significant influence between financial capital and financial inclusion on the performance of the hotel business in Bandung.